2006
DOI: 10.1158/1535-7163.mct-05-0375
|View full text |Cite
|
Sign up to set email alerts
|

Survivin, a cancer target with an emerging role in normal adult tissues

Abstract: Survivin, an inhibitor of apoptosis protein, is highly expressed in most cancers and associated with chemotherapy resistance, increased tumor recurrence, and shorter patient survival, making antisurvivin therapy an attractive cancer treatment strategy. However, growing evidence indicates that survivin is expressed in normal adult cells, particularly primitive hematopoietic cells, T lymphocytes, polymorphonuclear neutrophils, and vascular endothelial cells, and may regulate their proliferation or survival. In p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
365
0
10

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 432 publications
(386 citation statements)
references
References 136 publications
(145 reference statements)
11
365
0
10
Order By: Relevance
“…Furthermore, survivin has been also found in the nucleus and cytosol where the implication is that it has functions in mitosis regulation and apoptosis inhibition, respectively (Fortugno et al, 2002). Survivin is expressed in most common human cancers and although present during embryonic and foetal development, it is undetectable in a variety of adult tissues (Adida et al, 1998) and for this reason it is currently recognised as an important anticancer target (Fukuda and Pelus, 2006). For this purpose, multiple strategies have been successfully investigated, including the molecular antagonists such as antisense oligos, RNA inhibition, dominantnegative mutants, survivin-specific cytolytic T cells, a nonphosphorylatable survivin mutant Thr 34 -Ala (T34A), and most recently, binding interface mimetics (Olie et al, 2000;Andersen et al, 2001;Grossman et al, 2001;Kanwar et al, 2001;Mesri et al, 2001;Wall et al, 2003;Plescia et al, 2005).…”
mentioning
confidence: 99%
“…Furthermore, survivin has been also found in the nucleus and cytosol where the implication is that it has functions in mitosis regulation and apoptosis inhibition, respectively (Fortugno et al, 2002). Survivin is expressed in most common human cancers and although present during embryonic and foetal development, it is undetectable in a variety of adult tissues (Adida et al, 1998) and for this reason it is currently recognised as an important anticancer target (Fukuda and Pelus, 2006). For this purpose, multiple strategies have been successfully investigated, including the molecular antagonists such as antisense oligos, RNA inhibition, dominantnegative mutants, survivin-specific cytolytic T cells, a nonphosphorylatable survivin mutant Thr 34 -Ala (T34A), and most recently, binding interface mimetics (Olie et al, 2000;Andersen et al, 2001;Grossman et al, 2001;Kanwar et al, 2001;Mesri et al, 2001;Wall et al, 2003;Plescia et al, 2005).…”
mentioning
confidence: 99%
“…Overexpression of survivin, a member of the IAP family of proteins, is attributed to the chemoresistance of tumor cells (Adida et al, 2000;Fukuda and Pelus, 2006;Ryan et al, 2009;Feng et al, 2013). On the contrary, different studies have shown that suppression of survivin expression can sensitize tumor cells to anti-cancer drugs (Zaffaroni et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike other IAP members, survivin is largely expressed in embryonic and fetal tissues as well as in many malignant cells, but not in normal adult tissues (Zaffaroni and Daidone, 2002;Coumar et al, 2013). Previous reports have demonstrated that the overexpression of survivin is correlated with tumor progression, poor prognosis and drug resistance in many cancers including AML (Adida et al, 2000;Fukuda and Pelus, 2006). Because of this overexpression in cancer, its important role in apoptosis as well as cell division, and its association with drug resistance, survivin has been considered as an attractive therapeutic target in malignancies (Ryan et al, 2009;Feng et al, 2013).…”
Section: Sirna-mediated Silencing Of Survivin Inhibits Proliferationmentioning
confidence: 99%
“…20 Survivin is an IAP that appears to be more selectively expressed in malignant The results indicate that survivin may play a key role in tumorigenesis and progression of neuroblsatoma by its biologic activities of anti-apoptosis and angiogenesis. 23 However, it should be acknowledged that this study was retrospective, and therefore has limitations, e.g., in…”
Section: Discussionmentioning
confidence: 95%